The impact of different exercise protocols on rat soleus muscle reinnervation and recovery following peripheral nerve lesion and regeneration - Di Palma, Michael; Ambrogini, Patrizia; Lattanzi, Davide; Brocca, Lorenza; Bottinelli, Roberto; Cuppini, Riccardo; Pellegrino, Maria A.; Sartini, Stefano (Frontiers in Physiology, 2022)
Background: Incomplete functional recovery following traumatic peripheral nerve injury is common, mainly because several axons fail to regenerate and reinnervate target muscles. Exercise can improve functional outcomes increasing the terminal sprouting during the muscle reinnervation. However, exercise is not a panacea per se. Indeed, the type of exercise adopted dramatically impacts the outcomes of rehabilitation therapy. To gain insight into the therapeutical effects of neuromuscular activity during the reinnervation upon a traumatic nerve lesion, we evaluated the impact of different clinically transferable exercise protocols (EPs) on metabolic and functional muscle recovery following nerve crush. Methods: The reinnervation of soleus muscle in adult nerve-crushed rats was studied following six days of different patterns (continuous or intermittent) and intensity (slow, mid and fast) of treadmill running EPs. The effects of EPs on muscle fiber multiple innervation, contractile properties, metabolic adaptations, atrophy, and autophagy were assessed using functional and biochemical approaches. Results: Results showed that an intermittent mid-intensity treadmill EP improves soleus muscle reinnervation, whereas a slow continuous running EP worsens the functional outcome. However, the mid-intensity intermittent EP neither enhanced the critical mediator of exercise-induced metabolic adaptations, namely PGC-1α, nor improved muscle atrophy. Conversely, the autophagy-related marker LC3 increased exclusively in the mid-intensity intermittent EP group. Conclusions: Our results demonstrated that an EP characterized by a mid-intensity intermittent activity enhances functional muscle recovery upon a nerve crush, thus representing a promising clinically transferable exercise paradigm to improve recovery in humans following peripheral nerve injuries.